Delta-9-tetrahydrocannabinolic acid A (THC-A) in urine of a 15-month-old child: A case report. (May 2018) - Morini, Luca; Quaiotti, Jessica; Moretti, Matteo; Osculati, Antonio Marco Maria; Tajana, Luca; Groppi, Angelo; Vignali, Claudia
Highlights: Simple method to identify and quantify THC-A and CBD-A in urine. THC-A and CBD-A not detected in urine of active smokers. First case of detection of THC-A in a 15-month-old child. Presence of THC-A in urine to assess a cannabis preparation ingestion. Abstract: Introduction: The acidic forms of cannabinoids, THC-A and CBD-A are naturally present in cannabis plants and preparations and are generally decarboxylated to the active compounds before the use (e.g. thermally decarboxylated through smoking). Hence, the identification of the acidic compounds in urine could be an evidence of cannabis ingestion rather than a passive exposure to smoke. This case report described a 15-month-old child that suffered an acute intoxication by accidental cannabis ingestion. It is important to assess the ingestion and to discriminate it from a passive exposure to better interpret the clinical findings and to establish the correct therapeutic procedure. Methods: Urine samples were simply diluted in deionized water and directly injected in the LC–MS/MS system. D3 -THCCOOH was used as internal standard. Chromatographic separation of THCCOOH, THC-A and CBD-A was carried out in reversed phase on a c18 column. A triple quad in MRM negative mode was used to monitor the three analytes. Results and discussion: The developed LC–MS/MS method was simple and fast. A LOD of 3.0 ng/mL and a LOQ of 10.0 ng/mL were measured for the three compounds. The analytical procedure was validated accordingly to international guidelines. The two urine samples collected from the 15-month-old child at the hospitalization and after three days provided positive results for THCCOOH (130.0 and 10.0 ng/mL respectively). THC-A was found only in the urine sample collected at the hospitalization (concentration: 70.0 ng/mL). Conclusion: THC-A was detected and quantitated in a urine sample of a 15-month-old child.